2023
DOI: 10.1038/s41531-023-00497-x
|View full text |Cite
|
Sign up to set email alerts
|

Using a smartwatch and smartphone to assess early Parkinson’s disease in the WATCH-PD study

Abstract: Digital health technologies can provide continuous monitoring and objective, real-world measures of Parkinson’s disease (PD), but have primarily been evaluated in small, single-site studies. In this 12-month, multicenter observational study, we evaluated whether a smartwatch and smartphone application could measure features of early PD. 82 individuals with early, untreated PD and 50 age-matched controls wore research-grade sensors, a smartwatch, and a smartphone while performing standardized assessments in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 54 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…We did not assess patients off medication or compare naive patients to those on medications or assess treatment effects. These and other important questions should be addressed in ongoing 42,45,50 and future studies. Nonetheless, this is one of the largest studies investigating digital mobility technology in PD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We did not assess patients off medication or compare naive patients to those on medications or assess treatment effects. These and other important questions should be addressed in ongoing 42,45,50 and future studies. Nonetheless, this is one of the largest studies investigating digital mobility technology in PD.…”
Section: Discussionmentioning
confidence: 97%
“…Our longitudinal cohort was relatively small. Future work such as in the Personalized Parkinson Project, 49 Mobilise-D project, 45 and WatchPD 50 will further explore these findings and the prognostic value of digital mobility measures. We did not assess patients off medication or compare naive patients to those on medications or assess treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…Smartwatch and smartphone-based cognitive assessments serve as a tool to measure cognition in real-time outside of the clinic environment, as cognition may fluctuate with exercise, sleep, stress, and social settings ( Hays et al, 2019 ). A 12-month longitudinal study explored monitoring of cognitive and psychomotor functioning in PD via smartphone app, BrainBaseline ( Adams et al, 2023 ). PD subjects and healthy controls performed cognitive batteries such as Trail Making Test Part A, assessing complex attention, and Symbol Digit Modalities Test, assessing psychomotor speed.…”
Section: Nonmotor Systemmentioning
confidence: 99%
“…Studies have shown that there are differences in brain activity loss between patients with different dominant hand preferences in PD and found that the genetic variants contribute to neurodevelopmental lateralization of brain organization, which in turn influences both the handedness phenotype and the predisposition to develop certain neurological and psychiatric diseases based on genotypes and brain image scans of about 9,000 participants from more than 400,000 people ages from 40 to 69 selected from the UK Biobank [17,18]. Our previous study also has demonstrated a significant difference in step counts, which serve as an important means of quantifying declining ambulatory behavior associated with disease progression, between righthanded versus left-handled or ambidextrous PD patients [19]. Handedness's potential influence on PD has only recently gained attention and as of the most recent data available, there is limited research and a scarcity of relevant papers on the subject.…”
Section: Introductionmentioning
confidence: 99%